The history of theatre - Gibson, Thomasina; Coveney, Alan (United Kingdom : Classroom Video, 2009)
The essence of good theatre is simplicity itself, believeable characters, gripping stories and a seamless, convincing product. To understand how to achieve this we need to understand the roots of theatre. In this engaging and informative program, we take a comprehensive look at the history of theatre and drama, taking students from the ancient Greeks to the medieval Mystery plays, from the Renaissance to the Restoration, finishing up with Modern Theatre, exploring different play styles, staging and acting.
Executive producer, Lynn Ovens
Presenter, Jay Oliver Yip
Keywords: Theater -- History